UPAYA GURU DALAM MENIGKATKAN KOMPETENSI PROFESIONAL - Ahmad Mursyid (Tsaqofah: Jurnal Pendidikan Islam, 2021)
Law No. 14 of 2005 concerning Teachers and Lecturers states that "teachers are required to have academic qualifications, competencies, teacher certificates, are physically and mentally healthy, and have the ability to realize the goals of national education, the competencies referred to include pedagogical competence, personality competence, social competence, professional competence.The four aspects cannot stand alone, but are interrelated and influence one another. It is not easy to master and apply it to learning. Therefore, teachers must always learn and try new things that support their own development, besides that individual abilities can develop through training, practice, group work, and independent learning The research focus in this thesis is: How are the teachers' efforts in improving pedagogical, personality, social and professional competence. This study aims to: describe the teacher's efforts to improve pedagogical, personality, social and professional competence a To obtain data, a qualitative research approach was used which was described descriptively by the method of observation, interview and documentation which would be analyzed using a qualitative descriptive reflective method. Teachers have carried ot teaching tasks which include teaching preparation, teaching process and carrying out duties as administrator properly, this can be seen in the making of lesson plans, implementing process learn and teach and carrying out evaluations effectively. Teacher personality competence . Efforts made to improve the social competence of teachers are following education and training in social fields, training themselves by participating in social activities both at school and in the community. Another social aspect can also be seen from the good relationship between teachers and teachers, employees, and the principal. Efforts made to improve professional competence include attending education and training, attending subject teacher meetings (MGMP), workshops, updating information related to subject matter and other activities that have contributed to increasing professional competence